EFFECT OF DIFFERENT COLCHICINE CONCENTRATIONS ON CHROMOSOME POLYPLOIDY BEHAVIOR OF GALL OAK (QUERCUS INFECTORIA OLIV.) BY USING MOLECULAR BIOLOGY - ATROUSHI, HISHYAR HAZIM; SULEIMAN, FAROQ YOUSSEF (Journal of Duhok University, 2023)
Gall oak has a large ecological adaptability landscape and social importance and it is share of the natural wealth and has great economic value. Polyploidy deducted in this study through pre-screened directly by determining stomata guard cell length then confirmed by quantifying the DNA content using SCoT-PCR analysis. Depending in the stomata length as method we found the maximum of tetraploids (4n) and mixoploids (3n) plants were induced in chlciploidy treatments 2000 and 3000 mgl-1 of colchicine and soaked for 96 h. and 24 h. SCoT-PCR can detect polyploidy in the Gall Oak and provides an alternative method for analyzing polyploid genotype and breeding. Ungerminated seeds increased with increasing colchicine concentrations and exposure period especially in colchiploidy (2000 and 3000 mgl-1 for 72 and 96 h.) as a result of the toxicity of the colchicine substance. Significant differences were observed between polyploids and diploids plants. The tetraploid plants, show superiority in it is phenotypical treaties were created taller and thicker seedlings stems and roots, had more yields of branch, leaves and roots per seedlings, thicker leaves and bigger leaves. Whereas, chemical and physiological characteristics, significant contents of chlorophyll increased in polyploid plants, which leads to greener leaf color, but decreased in the of tannins amount. Also, the stomata guard cells size increased but decreased in number per area. Inducing novel features by ploidy breeding is a powerful tool that can lead to commercial success in forest tree species